Hypothermia in extracorporeal circulation in cardiac surgery - Carneiro, Tiago de Castro (2021)
This article aims to understand the importance of hypothermia during cardiopulmonary bypass. It emerges with the premise of understanding the importance of hypothermia induced in performing cardiac surgery with cardiopulmonary bypass (CPB), however, it is necessary to understand that the emergence of CPB in cardiac surgery was a milestone in the history of health, allowing the direct manipulation of the heart in many pathologies hitherto considered incurable. An integrative review methodology was used, with a search for existing articles in the literature. The search for articles was carried out between the months of June and August 2020. For the study, national articles published in full were used, the strategy of using each descriptor in isolation associated with the filters of interest available in the Virtual Health Library was adopted. (VHL), with LILACS (Latin American and Caribbean Literature in Health Sciences) and SCIELO (Scientific Electronic Library Online) databases, using the following descriptors: Hypothermia, Extracorporeal Circulation, Cardiac Surgery. We have identified an important point that this research supports, showing that temperature control during the operative process, both in the hypothermia period, is necessary to decrease metabolism. Hypothermia is a procedure that transcends our expectation, this makes it possible to stop circulation completely for an hour or more, and after warming up, see the patient return to his state of homeothermal metabolism and life. This study allowed a reflection on the performance of cardiac surgeries, disseminating knowledge about the importance of using hypothermia in this type of surgery. In conclusion, despite many technological advances, hypothermia still persists in not being used to avoid pathophysiological complications. Therefore, it is essential to describe the mechanisms that are positive in the use of hypothermia.